Guidelines on the Use of Systemic Therapy in Patients with Advanced Thyroid Cancer. Issue 1 (January 2023) - Wadsley, J.; Beasley, M.; Garcez, K.; Hoy, S.; Newbold, K.; Boelaert, K.
Abstract: With increasing understanding of the molecular alterations leading to thyroid cancers in recent years we have seen a rapid increase in the number of effective targeted systemic therapies available for patients with advanced thyroid cancer; firstly with the advent of the multi-kinase inhibitors and more recently with more specific RET, BRAF, MEK, ALK and NTRK inhibitors. Although these developments are very welcome, they have resulted in a paradigm shift in the management of advanced thyroid cancer to which thyroid oncologists have had to rapidly adapt, learning how to supervise treatment safely with novel agents, the management of novel toxicities, when and how to arrange molecular genetic testing of cancers and, perhaps most importantly, determining when the optimum time is to start these treatments in what can often be a relatively indolent, if progressive, disease. We hope that these guidelines will support clinicians in making these decisions with their patients, as well as signposting and providing useful supporting information both for patients and clinicians.